Campylobacter colitis. Issue 10 (October 1979) - Willoughby, C P; Piris, J; Truelove, S C
Abstract : A patient is described in whom a campylobacter enteritis closely resembled ulcerative colitis on clinical, sigmoidoscopic, and histological grounds. Selective stool culture techniques may be necessary to differentiate campylobacter colitis from ulcerative colitis proper.